PSIKOLOGI DAN ETIKA HUMANISTIK PADA TOKOH DALAM NOVEL DUR (DIARY UNGU RUMAYSHA) - Siti Nur Afifatul Hikmah; Yulia Ula Muhtari (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This research is motivated by the desire of the researcher to examine the DUR novel from a psychological perspective and is directed from the point of view of its humanistic psychology. This study aims to describe the need for humanistic psychology in characters and the humanistic ethics of characters in the novel DUR. The method used in the analysis is a descriptive qualitative method, with steps in the form of data reduction, analysis by comparison, data presentation, and verification. Based on data analysis, it can be concluded that Nisaul Kamilah's novel DUR is represented through aspects of humanistic psychology, the factors behind the character's ethical humanism, and the implications of the discussion on literary learning. The results of the analysis show that (1) aspects of humanistic psychology through the need for self-actualization have more power to dominate in the application of humanism, (2) there is a humanistic ethic in the characters of the novel DUR.